2011
DOI: 10.2139/ssrn.1555257
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Distribution of Inflation Rates: Functional Autoregressive Approach

Abstract: In line with the recent developments on the statistical analysis of functional data, we develop the semiparametric functional autoregressive (FAR) modeling approach to the density forecasting analysis of national inflation rates using sectoral inflation rates in the UK over the period January 1997-September 2013. The pseudo out-of-sample forecasting evaluation and test results provide an overall support to superior performance of our proposed models over the aggregate autoregressive models and their statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Our analysis of UK sectoral inflation draws heavily on Chaudhuri, Kim, and Shin (, henceforth CKS) . We utilize CKS's data set, which is based on subsector consumer price indices and the associated weights obtained from the Office for National Statistics.…”
Section: Stylized Factsmentioning
confidence: 99%
“…Our analysis of UK sectoral inflation draws heavily on Chaudhuri, Kim, and Shin (, henceforth CKS) . We utilize CKS's data set, which is based on subsector consumer price indices and the associated weights obtained from the Office for National Statistics.…”
Section: Stylized Factsmentioning
confidence: 99%
“…Additionally, Roger (2000) found evidence towards right skewness. In addition, Chaudhuri, Kim, and Shin (2011) found that the mean inflation is positively correlated with variance and skewness. These results suggest that a greater attention must be paid to increases than decreases of inflation rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although ARCH family models are quite useful in modelling time-series variation in conditional volatility, these models assume that the conditional distribution are time-varying only in the first two moments and ignore the information content in higher-order moments (Chaudhuri, Kim, and Shin, 2011). To fill this gap, Harvey and Siddique (1999) developed a new approach to estimate nonconstant conditional skewness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation